2019
DOI: 10.1177/1359105319883923
|View full text |Cite
|
Sign up to set email alerts
|

Living well with chronic illness: How social support, loneliness and psychological appraisals relate to well-being in a population-based European sample

Abstract: Positive social and psychological appraisals may help maintain well-being in illness, but few studies have systematically investigated this in a European context. After controlling for sociodemographic, health and objective social factors, we employed multilevel regression modelling to establish if appraisals predict well-being in three illness groups ( n = 10,577). In addition to health and financial status, positive appraisals were consistent predictors of well-being. Social appraisals had stronger associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…In contrast, positive efficacy expectations may be more useful when self-care is possible (Fournier et al, 2002). Similar effects have been observed in other chronic illness populations, with optimism showing stronger associations with QOL in those limited by disease, compared to those who are not (Maguire et al, 2019). While our review found similar benefits for self-efficacy expectations in a range of PwMS, including those with progressive forms of the disease, examination of the broader literature implies that the benefits of fostering positive expectations may depend on individual health-related characteristics and other contextual factors.…”
Section: Negative Focssupporting
confidence: 53%
See 1 more Smart Citation
“…In contrast, positive efficacy expectations may be more useful when self-care is possible (Fournier et al, 2002). Similar effects have been observed in other chronic illness populations, with optimism showing stronger associations with QOL in those limited by disease, compared to those who are not (Maguire et al, 2019). While our review found similar benefits for self-efficacy expectations in a range of PwMS, including those with progressive forms of the disease, examination of the broader literature implies that the benefits of fostering positive expectations may depend on individual health-related characteristics and other contextual factors.…”
Section: Negative Focssupporting
confidence: 53%
“…The focus of the review was patient-led, having been conceptualised by the first author, who has MS. The protocol was presented at the MS Frontiers Conference in July 2019 (Maguire et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…This finding strongly indicates having an emotional social support system is important for maintaining psychological wellbeing in people living with HIV [ 8 , 11 , 15 ]. The significance of emotional social support is a well-known fact also in other chronic [ 36 ] and acute [ 37 ] health condition as well as in the general population [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…With this cumulation of experiences throughout life, it is perhaps not surprising that some of our survey participants described becoming accustomed to their condition and using various coping strategies. A large population-based study identified that among those with chronic illness, optimism, and resilience appeared to be more important to those facing severe limitations to daily activities, than those who were not, suggesting that positive psychological appraisals play a key role in maintaining wellbeing when faced with debilitating illnesses [ 29 ]. Resilience can be defined as the ability to adapt one’s responses in the face of adversity and the associated stressors, and is a concept influenced by psychological, biological, and environmental factors [ 30 ].…”
Section: Discussionmentioning
confidence: 99%